2019
DOI: 10.1111/and.13499
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosol prevents AlCl3induced male reproductive damage by suppressing apoptosis and activating the Nrf‐2/HO‐1 pathway

Abstract: Aluminium is a ubiquitous element that occurs naturally in the soil making human exposure to it is unavoidable. Tyrosol is present in olive oil and is known to have antioxidant effects. Therefore, the present study explores the toxic effects of aluminium chloride (AlCl3) and evaluates the possible protection by tyrosol in male rats. Testicular injury was induced by the administration of AlCl3 (34 mg kg−1 day−1). Rats were treated with either tyrosol (20 mg kg−1 day−1) or AlCl3 (34 mg kg−1 day−1). The experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 66 publications
4
15
1
Order By: Relevance
“…In a study on rats, it was reported that NRF-2 was suppressed in the brain tissue after exposure to AlCl 3 (Sadek et al, 2019). Güvenç and colleagues reported that NRF-2 gene expression decreased in testicular tissues of rats exposed to AlCl 3 (Güvenç et al, 2020). Although these findings contradict with our results, it can be evaluated that the effect of AlCl 3 on NRF-2 expression affects the translation level rather than the transcription stage.…”
Section: Discussioncontrasting
confidence: 99%
“…In a study on rats, it was reported that NRF-2 was suppressed in the brain tissue after exposure to AlCl 3 (Sadek et al, 2019). Güvenç and colleagues reported that NRF-2 gene expression decreased in testicular tissues of rats exposed to AlCl 3 (Güvenç et al, 2020). Although these findings contradict with our results, it can be evaluated that the effect of AlCl 3 on NRF-2 expression affects the translation level rather than the transcription stage.…”
Section: Discussioncontrasting
confidence: 99%
“…However, it was determined that MDA in the Tyrosol treated group decreased to the levels of the control group. In the study conducted by Güvenç et al, it was reported that MDA increased in rats treated with AlCl 3 , whereas tyrosol treatment signi cantly decreased the MDA level (Güvenç et al 2020). GSH is an important cellular antioxidant that prevents the redox cycle and free radical formation (Martínez-Martos et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Cheraghi et al also reported the effect of AlCl 3 on sperm count, and in his study, the AlCl 3 -administered group showed > 50% reduction in the number of sperm cells compared to the control group [18]. The quality of the sperm including motility and viability is also affected by Al via the Nrf-2/ HO-1 signaling pathway [18,43]. In this study, the animals administered with AlCl 3 + vitamin C and AlCl 3 + EGCG showed a qualitative reduction in the number of sperm cells when compared to the control group, but the results were not significant.…”
Section: Discussionmentioning
confidence: 99%